2021
DOI: 10.3390/ph14020137
|View full text |Cite
|
Sign up to set email alerts
|

miR-16-5p Promotes Erythroid Maturation of Erythroleukemia Cells by Regulating Ribosome Biogenesis

Abstract: miRNAs constitute a class of non-coding RNA that act as powerful epigenetic regulators in animal and plant cells. In order to identify putative tumor-suppressor miRNAs we profiled the expression of various miRNAs during differentiation of erythroleukemia cells. RNA was purified before and after differentiation induction and subjected to quantitative RT-PCR. The majority of the miRNAs tested were found upregulated in differentiated cells with miR-16-5p showing the most significant increase. Functional studies u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…Merkerova et al (2008) found that miR-16 was highly expressed in most human hematopoietic cells [ 6 ]. There are similar reports regarding miR-16-5p [ 66 ]. Although miR-16–2 is associated with polychromatic erythroblast differentiation, details of their role have not been established yet [ 4 ].…”
Section: Mirna Regulation In Erythropoiesis (Table 2 ...supporting
confidence: 75%
“…Merkerova et al (2008) found that miR-16 was highly expressed in most human hematopoietic cells [ 6 ]. There are similar reports regarding miR-16-5p [ 66 ]. Although miR-16–2 is associated with polychromatic erythroblast differentiation, details of their role have not been established yet [ 4 ].…”
Section: Mirna Regulation In Erythropoiesis (Table 2 ...supporting
confidence: 75%
“…* When the Ct values were undermined due to very low expression, a value of 40 was denoted for calculation. References [ 9 , 20 , 22 , 32 , 41 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 ] are referred to in the Supplementary Material file.…”
mentioning
confidence: 99%
“…By knockdown of miR‐16‐5p, we proved that miR‐16‐5p is essential for promoting aerobic glycolysis during sepsis. miR‐16‐5p directly binds to multiple target genes and modulates their expression (Cai et al, 2018; Papagiannopoulos et al, 2021; Qu et al, 2018; Ruan & Qian, 2019). However, its target in the macrophage, especially during infection, remains elusive.…”
Section: Discussionmentioning
confidence: 99%